Role of Teaching Effectiveness in Emerging Education Scenario: Exploring the Impact of Teaching Effectiveness in the Changing Education Landscape (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In olden days it was believed that a person with high Intelligence Quotient (IQ) and mastery over the subjects could be a successful teacher but now teaching profession has become so challenging that a teacher with high IQ and mastery over the subjects may not be successful unless he or she has teaching effectiveness. Since the change is the law of nature so teaching profession is controlled by several external factors such as class size, number of teachers in institution, working hours, salary and allowances and education policy. The intrinsic factors such as mastery of subject, style of teaching, communication skill and personality of teacher also affect teaching learning process.The term teaching effectiveness is not defined unambiguously, precisely and explicitly but most of the authors and scholars have made efforts to explain the teaching effectiveness on the basis of traits and characteristics required for effective teachers. Further different authors have perceived teaching effectiveness in different ways so they have expressed teaching effectiveness in their own sense. The word teaching effectiveness is consisted of two words i.e. “Teaching” and “Effectiveness”. By and large authors have defined teaching effectiveness on basis of personality and qualities of effective teachers. Some definitions are based on general effectiveness of teacher while others are based on teaching traits and behaviour of a teacher. But it has been observed that general effectiveness achieving the academic goals with use of minimum resources and in time. However the teaching effectiveness will be proved a better construct of education if applied along with emotional intelligence, self-efficacy, job satisfaction and multiple intelligences.